Null and overt se constructions in Brazilian Portuguese and the network of se constructions - Afonso, Susana (2024)
Middle voice (MV) comprises a set of marked constructions associated with situation types (Kemmer 1993. The middle voice. Amsterdam: John Benjamins), in which the middle marker functions as an intransitivizer. MV constructions in Portuguese are se constructions in which the clitic se is typically overt, but in Brazilian Portuguese there is variation between constructions with and without the clitic marker. The overt-null variation is observed in all se construction types and it has been argued by Soares da Silva et al. (2021. Null se constructions in Brazilian and European Portuguese: Morphosyntactic deletion or emergence of new constructions? Cognitive Linguistics 32(1). 159-193) that differences in conceptualization of an event as "energetic"or "absolute"primarily drive the variation. This article focuses on the (re)configuration of the network of se constructions in light of the overt-null alternation. Given that the alternation is systematic for all types of se construction, we propose that both the marked and unmarked constructions are plotted onto the conceptual map of MV constructions. As to the introduction of the null variant in the taxonomy of se constructions, we argue that the overt-null variants are allostructions posited at lower levels of abstraction. We also hypothesize that the middle marker at the top node is underspecified for function, instantiated as an intransitivizer, or lexically defined at the immediate subordinate level.